Adults' dental treatment in 2001-2013 in Finnish public dental service - J. Linden; E. Widström; J. Sinkkonen (BMC, 2020)
Abstract Background All adults over 17 years of age have access to the Public Dental Service after the Finnish Dental Care Reform in 2001-2002. This study aimed to survey the treatment needs and treatment measures provided for adult patients and changes in these during the period 2001-2013. Methods Sing each person's unique identifier, demographic data on dental visits during the period 2001-2013 were collected from municipal databases in five PDS-units covering 320,000 inhabitants. The numbers of visitors, those in need of basic periodontal or caries treatment (CPI > 2 and D + d > 0) were calculated for three age groups. Treatment provided was also calculated in 13 treatment categories. Trend analyses were performed to study changes during the study period. Results Restorative treatments (968,772; 23.6%), examinations (658,394; 16.1%), radiographs taken (529,875; 12.9%) anaesthesia used (521,169; 12.7%) and emergency treatments (348,229; 8.5%) made up 73.8% of all treatment measures during the entire study period. Periodontal treatment (7.8%) and caries prevention (3.9%) made up a small part of the care provided and prosthetics and treatment of TMJ disorders were extremely uncommon (fewer than 1%). Treatments related to caries (restorative treatment, examinations, endodontics, emergencies, anaesthesia and radiographs) made up 60.4% of the dental personnel's treatment time. During the study period, statistically significant increasing trends were found for radiographs (p < 0.001***), anaesthesia (p = 0.003**) and total number of treatments (p = 0.009**). There was a slight decreasing trend in treatment need among the youngest adults (18-39 years; p = 0.033*). Conclusion Compared with the results of national epidemiological studies, insufficient periodontal treatment is provided and prosthetic treatment is almost totally neglected in the PDS. Rather, adults' dental treatment concentrates on treatment of caries. The unmet needs may be due to tradition, inadequate treatment processes or a lack of resources or failed salary incentives.